Центробежная неустойчивость течения в пористом криволинейном канале - Авраменко, A.A.; Сорокина, Т.В.; Басок, Т.Б. (Видавничий дім "Академперіодика" НАН України, 2007)
The problems of the centrifugal instability of a flow in the porous curvilinear channel are considered. The criteria of the longitudinal vortex appearance are obtained as Dean numbers. The influence of the channel width and the medium porosity on values of the Dean critical numbers and wave numbers is investigated.